Pengaruh Kepemimpinan, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan - Riska Winanda; Yohny Anwar (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study aims to test and find out more clearly how leadership, work motivation and work discipline influence employee performance at the Medan City Market Public Company. This study uses a quantitative method involving 88 respondents. Data collection was carried out using a questionnaire distribution. The data obtained were analyzed using a statistical formula, namely by using multiple regression analysis which was processed using the SPSS Version 23 program. The results of the study indicate that leadership partially has a positive and significant effect on employee performance. The results of the study indicate that work discipline partially has a positive and significant effect on employee performance. leadership, work discipline and work discipline simultaneously have a positive and significant effect. 57.2% of employee performance can be explained and obtained from leadership, work discipline and work discipline while the rest is by other factors. Employee performance has a strong relationship to leadership, work motivation and work discipline.